Mutation in Bombyx mori fibrohexamerin (P25) gene causes reorganization of rough endoplasmic reticulum in posterior silk gland cells and alters morphology of fibroin secretory globules in the silk gland lumen. (August 2021) - Zabelina, Valeriya; Takasu, Yoko; Sehadova, Hana; Yonemura, Naoyuki; Nakajima, Kenichi; Sezutsu, Hideki; Sery, Michal; Zurovec, Michal; Sehnal, Frantisek; Tamura, Toshiki
Abstract: Larvae of many lepidopteran species produce a mixture of secretory proteins, known as silk, for building protective shelters and cocoons. Silk consists of a water-insoluble silk filament core produced in the posterior silk gland (PSG) and a sticky hydrophilic coating produced by the middle silk gland (MSG). In Bombyx mori, the fiber core comprises three proteins: heavy chain fibroin (Fib-H), light chain fibroin (Fib-L) and fibrohexamerin (Fhx, previously referred to as P25). To learn more about the role of Fhx, we used transcription activator-like effector nuclease (TALEN) mutagenesis and prepared a homozygous line with a null mutation in the Fhx gene. Our characterization of cocoon morphology and silk quality showed that the mutation had very little effect. However, a detailed inspection of the secretory cells in the posterior silk gland (PSG) of mid-last-instar mutant larvae revealed temporary changes in the morphology of the endoplasmic reticulum. We also observed a morphological difference in fibroin secretory globules stored in the PSG lumen of Fhx mutants, which suggests that their fibroin complexes have a slightly lower solubility. Finally, we performed an LC-MS-based quantitative proteomic analysis comparing mutant and wild-type (wt) cocoon proteins and found a high abundance of a 16 kDa secretory protein likely involved in fibroin solubility. Overall, our study shows that whilst Fhx is dispensable for silk formation, it contributes to the stability of fibroin complexes during intracellular transport and affects the morphology of fibroin secretory globules in the PSG lumen. Graphical abstract: Image 1 Highlights: A knockout silkworm line lacking fibrohexamerin (Fhx) has been generated. Fhx deletion has no obvious effects on silkworm viability or cocoon morphology. Posterior silk gland cells lacking Fhx display altered endoplasmic reticulum. Secretory silk globules in Fhx mutants appear abnormally compact. Mutant cocoons contain increased levels of a protein likely involved in fibroin solubility.